2008
DOI: 10.1002/jgm.1226
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of radiation‐induced skin injury by AAV2‐mediated MnSOD gene therapy

Abstract: The proof-of-concept demonstrated in the present study together with the known safety profile in humans indicate that AAV-mediated MnSOD expression has potential countermeasure utility against normal tissue injury following radiation therapy or radiological accident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…These results indicate the marked relief of IR-induced skin injury provided by Mn-SOD expression (32). Because of the high radiosensitivity, it is obvious that hematopoietic cell proliferation can be suppressed upon the exposure to radiation (33).…”
Section: Radioprotection At the Tissue Or Organ Levelmentioning
confidence: 73%
“…These results indicate the marked relief of IR-induced skin injury provided by Mn-SOD expression (32). Because of the high radiosensitivity, it is obvious that hematopoietic cell proliferation can be suppressed upon the exposure to radiation (33).…”
Section: Radioprotection At the Tissue Or Organ Levelmentioning
confidence: 73%
“…It has been estimated that 66% of damage caused by radiation is due to free radicals generated during radiation and that 33% of the damage results from persistent postirradiation oxidative stress (63). Given the known bioactivity of the SOD mimetics and the postirradiation administration of the drugs, we think it is highly unlikely that these compounds reduce direct radiation-induced DNA damage but that instead it is likely that they reduce the activity of long-lived radicals and scavenge new radicals generated by secondary biochemical events hours to days after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted in vitro and in vivo have demonstrated that several agents can increase survival of cells or animals when administered after exposure to lethal doses of radiation (3032). For example, lethally irradiated embryonic cells treated up to 1 h postirradiation with a nitroxide, hemigramicidin-TEMPO, had significantly improved clonogenic survival (30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example adeno-associated virus (AAV), first used in 1984 [15][16][17], is known to actively express transduced genes for 22 months in mice and 10 years in humans [18,19]. Gene delivery/gene therapy, utilizing a variety of virus types, has delivered antioxidant genes into cells and animals, however most of these studies have limited to the delivery of various forms of SOD or catalase [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%